The Effect of Quizizz on Indonesian Language Learning in the Independent Curriculum - Adi Rahman; Asri Yulianda; Eko Firman Susilo (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to assess the effectiveness of the Quizizz application in Indonesian language learning based on the Independent Curriculum at SMA Muhammadiyah 10 Rantauprapat. The study was motivated by the low learning interest and academic performance of students in Indonesian language subjects, along with the limited use of digital learning media suited to the needs of today’s learners. The research employed a quasi-experimental design using a pretest-posttest control group model. The participants were two eleventh-grade classes, one taught using Quizizz-assisted learning and the other through conventional instruction. The findings revealed a significant improvement in student learning outcomes in the experimental class, where the average posttest score increased from 62.1 to 81.4, compared to an increase from 61.5 to 72.3 in the control class. The t-test result showed a significance value of 0.001 (<0.05), confirming a meaningful difference between the two groups. Observation results also indicated that students in the experimental class were more active and engaged during lessons. The novelty of this study lies in its focus on integrating Quizizz specifically within the context of the Independent Curriculum, emphasizing its alignment with learner-centered, technology-based, and interactive pedagogical principles. Thus, the use of Quizizz proved effective in improving both student achievement and participation, making it a relevant and practical learning medium in the current digital education era.